Pemberontakan OPM-KKB dalam Perspektif Etika Keutamaan Alasdair Calmers Maclntyre - Aprilia Budi Jansent Armandany; Krispianus Alfa Wewake Sarhe; Pius Pandor (Jurnal Filsafat Indonesia, 2023)
The focus of this paper is to explain the issue of the OPM-KKB rebellion against the TNI-Polri and civilians in Papua based on the ethical virtues of Alasdair Calmers MacIntyre. This act of rebellion was considered meaningless because it had a negative impact on civil society, the TNI-Polri, and the integrity of the Unitary State of the Republic of Indonesia. According to Macintyre, the meaningfulness of an activity is related to honesty, trust, justice, and courage. This ethical virtue is important in creating the stability of shared life, especially in the context of the plurality of the Indonesian nation. The method used in this study is a literature study by exploring the news about the OPM-KKB rebellion which is contained in mass media such as newspapers, magazines, television, and the internet. The results showed that the OPM-KKB rebellion was meaningless based on Alasdair Calmers MacIntyre's concept of thought, because it did not meet the requirements of honesty, trust, justice and courage. In an effort to address this issue, several contributions from MacIntyre and researchers can be implemented. First, through narrative reconstruction to restore awareness that humans always interact and unite with other people in their lives, so that rebellions like the OPM-KKB are not repeated and individuals have clear goals in life. Second, by strengthening tradition, historical values that shape human consciousness as part of history can be realized and applied in common life. Third, through character education which aims to reduce the OPM-KKB rebellion movement and prevent provocation to the younger generation in Papua to join the movement, so that they love the land of the Republic of Indonesia even more. Through character education based on ethical virtues, the values of honesty, trust, justice and courage can be realized. In overcoming this problem, approaches through narrative reconstruction, strengthening traditions, and character education are important steps to create stability in living together and loving the homeland of the Unitary State of the Republic of Indonesia